Design and comparative analysis of three phase, four phase and six phase switched reluctance motor topologies for electrical vehicle propulsion - Sandeep Vuddanti; Vinod Karknalli; Surender Reddy Salkuti (Institute of Advanced Engineering and Science, 2021)
Switched reluctance motor (SRM) is attracting the scientific community in recent days because of its special structural benefits. Good research work has been conducted on this machine since the ages. It has evolved as an alternative to the conventional electrical machines in variable speed drives due to rugged architecture, high-speed operation, four quadrants, lack of magnet, and adaptability to harsh surroundings. This paper reviews different topologies of SRM for electric vehicle (EV) application and a comparative study of suitable machines for electric vehicle propulsion. This paper elaborates on the design methodology and the analysis of various phases of operation of SRMs. During the design procedure, the finite element method (FEM) of optimization is used to enhance motor performance. In this study, the three different phase (3, 4 and 6) motors are analyzed in machine design software and finite element analysis outcomes and SRM simulation approach are discussed.